Iranian women working in broadcast media: motivations, challenges and achievements - Ghasemi, Asemeh (2014)
This research is premised on the investigation of Muslim women working in the Iranian Radio and Television Organisation (IRIB). The study is structured on a number of principal questions: why these women joined IRIB and how they managed the reactions of sceptical family members; how they construct the meaning of womanhood in relation to work, family and motherhood; what challenges these women encounter in the workplace; and how they negotiate and persevere to overcome those challenges, achieve success and make changes in a male-dominated organisation. The main focus is on the post-1979 Islamic revolution, when many practicing Muslim women, who were largely excluded from the film and media industries before the Revolution, began working in radio and television. Modern media that were considered instruments of ‘westernisation’ and ‘decadence’ before the Revolution were re-legitimised by religious authorities and even elevated to the status of ‘public universities’. Many Muslim women, therefore, entered this male dominated ‘forbidden space’ that had a largely secular and liberal work culture before the Revolution. Through 30 semi-structured interviews with these women, this research examines gender relations within the workspace, family domain and in the public arena. The research manifests complex dynamics of gender relations in the context of Iran and in the IRIB organisation. It argues that gender is a relational concept; and an area of constant negotiation and contest. In particular, the study demonstrates that gender relations are defined in negotiation with religious beliefs, traditional norms and political ideologies. They are also reinforced in the family and embedded in the culture of organisation. Overall, it is concluded that after the Islamic revolution, Muslim women found new opportunities to enter spaces in the public domain that were previously considered as being ‘inappropriate’ for women. Despite confronting many challenges in this respect, they have exercised their agency and achieved considerable success in changing traditional and prejudiced attitudes within structures that are underpinned by Islamic gender ideology. In doing so, they have also constructed a new identity of Muslim women that goes beyond simplistic stereotypical dichotomies such as liberated/oppressed, western/eastern, and secular/Muslim.